Nuclear ITS/ETS sequence data indicate the membership of Senecio racemulifer, but not S. acutipinnus and S. graciliflorus, within the genus Jacobaea (Asteraceae, Senecioneae) - Fei, Wen-Qun; Li, Hui-Min; Ren, Chen; Yang, Qin-Er (Phytotaxa, 2021)
The sectional placement of Senecio racemulifer (Asteraceae, Senecioneae) and the generic affiliation of S. acutipinnus and S. graciliflorus have been in dispute. Senecio racemulifer was tentatively considered a member of S. sect. Doria, and S. acutipinnus and S. graciliflorus were transferred to the genus Jacobaea as J. acutipinna and J. graciliflora, respectively. Our phylogenetic analyses based on nuclear ITS/ETS sequences indicate that S. racemulifer is deeply nested with Jacobaea species in a well-supported clade while S. acutipinnus and S. graciliflorus are nested with other Senecio species in a well-supported clade. We therefore transfer S. racemulifer to Jacobaea as J. racemulifera but retain S. acutipinnus and S. graciliflorus within Senecio. The names Jacobaea acutipinna, J. graciliflora, J. sect. Graciliflorae and S. ser. Racemuliferae are all synonymized. Karyological characters are reported for the three species. Jacobaea racemulifera, earlier known from the Western Tian-Shan (Kazakhstan, Kyrgyzstan, Uzbekistan), is reported here as new to China.